Audio plant condition monitoring. - Bruce Blakeley (2001)
Accelerometers are widely used in plant condition monitoring (PCM) to diagnose faults in rotating machinery. This can be expensive, and is typically only used to monitor the condition of critical machines. The objective of this project is to develop a system, using microphones, that could screen less critical machines for faults. Microphones are non-contact sensors that can be placed away from the machines, to avoid damage. If the data gathered by the microphone is reduced to a single parameter, that increases with wear, then analysis would be greatly simplified. This system could be used to provide basic PCM screening for equipment not considered important enough for routine vibration monitoring. To achieve this objective, a test-rig was designed and constructed, consisting of a motor, gearbox and load. Various faults were introduced into the test-rig, and a microphone used to record the sound. These results were then compared to accelerometer readings. Time synchronous averaging (TSA) was employed to increase the signal to noise ratio. It was proven that Kurtosis and crestfactor of a microphone signal both increase, if used with a high pass filter, when an impacting fault such as a broken gearbox tooth was introduced into the test-rig. It proved harder to reduce the sound of other non-impacting faults, such as misalignment, into a single parameter. The technique was tested in an industrial environment with a 100 dB background noise level. It was shown that the technique was capable of detecting faults even with a signal to noise ratio of -15 dB. A one dimensional FEA model was created, with six degrees of freedom, modelling the test-rig's vibrational behaviour. This was used to investigate the affect of a broken tooth, and to explain the increase in noise as the tooth passing frequency coincided with a resonance.